Contact resistance reduction of carbon nanotube via through O2 plasma post-synthesis treatment. Issue 18 (1st May 2018) - Li, Suwen; Liu, Yanghui; Zhou, Shaolin; Zhou, Changjian; Chan, Mansun
Abstract : A less invasive oxygen plasma post-synthesis treatment to reduce the contact resistance of CNT vias. Abstract : The cause of high contact resistance between carbon nanotube (CNT) filled vias and metal electrodes is studied. Contamination due to the chemical–mechanical polishing (CMP) process, which damages the sp 2 bonds at the end of the CNTs, is found to be the main cause. An alternative oxygen plasma etching process is proposed to preserve the sp 2 bonds at the CNT tips during the via planarization process. The improved properties of the CNT tips, with more sp 2 bonds and fewer oxygen-containing groups, have been demonstrated using X-ray photoelectron spectroscopy (XPS). Based on the findings, a new CNT via integration process is designed, which includes selective CNT growth inside the via and O2 plasma planarization. A low contact resistance of 1.83 μΩ cm 2 is demonstrated.